UTILIZATION OF COAL BOTTOM ASH AS BRIQUETTE MATERIAL - Ninis Hadi Haryanti; Suryajaya Suryajaya; Henry Wardhana; Rijali Noor (Program Studi Fisika Universitas Negeri Jakarta, 2019)
Research has been carried out on the use of coal bottom ash as a material for making briquettes as an alternative fuel. Carbonized of rubber seed shells and Halaban wood were used as mixtures and tapioca flour as adhesives. The composition used in making Halaban wood charcoal and coal bottom ash briquettes is 100% : 0%, 90% : 10%, 80% : 20%, and 70% : 30%. Tapioca flour used was as much as 5%, the pressure of 150 kg/cm2 and the size of 250 meshes. While for rubber seed shell and coal bottom ash briquettes, the composition used was with ratio 60% : 40% and 70% : 30%, the pressure used was 100, 150, and 200 kg/cm2 and the size of 50 meshes. Tapioca flour used was as much as 5%. The results of the characterization of rubber seed shell and coal bottom ash briquettes were water content (4.35 - 10.65)%, ash content (12.53 - 17.26)%, and calorific value (3597.59 - 4549.88) cal/g. While the characterization results of Halaban wood charcoal and coal bottom ash briquettes were water content (2.947 – 4.097)%, ash content (0.383 – 26.667)%, and calorific value (4749-6621) cal/g. The results showed that if coal bottom ash in the composition were higher, it would increase the water content and ash content of the briquettes, while the calorific value would be lower. The recommended composition of coal bottom ash was about 10-20 %. While if the briquettes pressure was higher, the water content, ash content and calorific value would be smaller. The recommended pressure was 150 kg /cm2.